CIRI BUDAYA AUSTRONESIA DI KAWASAN ENREKANG SULAWESI SELATAN - Nani Somba (WalennaE, 2010)
Enrekang is one of the regencies in South Sulawesi which having less attention in archaeological research. The research of Collo sites shows some of its importance, that is an old abandoned settlement and a shelter burial. The findings at Bambapuang's region, especially from Collo site seems showing its relationship with the character of early agricultural tradition while keep inheriting the late-Neolithic stone tools tradition. The basic character of the cultures in Bambapuang region relates with flakes technology, pottery, and ancestor's worship. The preliminary conclusion from all of the researches in Enrekang is that the first chronology of the settlement growth in Bambapuang Regency--especially at Collo site was at the same period with the spread of Austronesia in Nusantara Archipelago.Enrekang adalah salah satu kabupaten di Sulawesi Selatan yang kurang perhatian dalam penelitian arkeologi. Penelitian situs Collo menunjukkan beberapa aspek pentingnya, yaitu pemukiman tua yang ditinggalkan dan pemakaman. Temuan di wilayah Bambapuang, terutama dari situs Collo tampaknya menunjukkan hubungannya dengan karakter tradisi pertanian awal sambil tetap mewarisi tradisi alat-alat batu Neolitik akhir. Karakter dasar budaya di wilayah Bambapuang terkait dengan teknologi serpih, tembikar, dan pemujaan leluhur. Kesimpulan awal dari semua penelitian di Enrekang adalah bahwa kronologi pertama pertumbuhan permukiman di Kabupaten Bambapuang - terutama di lokasi Collo - adalah - pada periode yang sama dengan penyebaran Austronesia di Kepulauan Nusantara.